Subtitling Strategies and Acceptability of Humour in “Modern Family” Season 6 (2014) - Rahima Azim; Raden Pujo Handoyo; Nadia Gitya Yulianita (J-Lalite: Journal of English Studies, 2023)
This research aims to analyse the types of verbal humour, the subtitling strategies, and its acceptability in Modern Family Season 6. The research is conducted by using the theory of verbal humour translation by Raphaelson-West (1989), theory of subtitling strategies by Gottlieb (1992) and the theory of translation acceptability proposed by Nababan (2012). This research uses descriptive qualitative method. In the process, this research utilizes a questionnaire with inputs from raters as a consideration in analysing the translation. The data are utterances containing verbal humour from Modern Family Season 6. The result shows the most frequent type is universal humour (45), followed by linguistic humour (19), and cultural humour (13). Furthermore, 8 out of 10 subtitling strategies are applied by the subtiler. The most dominant strategy is the paraphrase strategy (28), followed by transfer (15), expansion (11), condensation (10), deletion (6), imitation (4), transcription (2), and decimation (1). The acceptability level of the subtitle is acceptable in 69 data and less acceptable in 8 data. The object of the research proposes to serve humour in a usual relatable family interaction that is universal. However, the source language is English which has different grammatical, vocabulary, and syntactic rules than Indonesian. Thus, paraphrase strategy is the most frequently used to transfer the message naturally and appropriately to the target language rules without losing the humour. Hence, the subtitle of verbal humour in Modern Family Season 6 is natural and relevant to the Indonesian rules that conveys the meaning and preserve the humour aspects.